Evaluation of a porcine coproduct (pro-blend 75®) from slaughter plants as a protein source for starter pig diets - Lee, D.J.; Dunsford, B.R.; Herkelman, K.L.; Hahn, J.D.; Hancock, Joe D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Pellet durability index was greatest when animal protein products (dried whey, fish meal, spray-dried blood cells, and a porcine coproduct) were used in place of soybean meal. However, no differences occurred in ADG, ADFI, or F/G among segregated early-weaned piglets (10.1 lb) fed the various protein sources.
Keywords: Swine; Animal Protein; Soybean meal; Nursery pigs